Development of Arduino Based Intelligent Traffic Control System for Intersections in Akure, Nigeria - Reuben Ayodeji Bolaji; Olumuyiwa Samson Aderinola; Moses Ariyo Oladipo; Temitope Elizabeth Oguntelure; Michael Oluwagbenga Abanire; Joshua Imoleayo Bolaji (Popular Scientist, 2025)
Traffic congestion at urban intersections remains a major challenge, causing delays, fuel waste, economic losses, and environmental pollution. Conventional traffic control systems are limited by fixed signal timing and their inability to adapt to real-time traffic demand. This study proposes an Arduino-based Intelligent Traffic Control System (ITCS) that integrates infrared sensors with Arduino Uno microcontroller to detect actual vehicle flow and adaptively allocate right of way. Applied to the Araromi intersection, simulation results showed that the ITCS introduced two key innovations of gapping out and maxing out. Unnecessary delays on low-demand approaches during off-peak periods were eliminated, while green times were extended till maximum only when queued vehicles were detected during peak hours. These features ensured efficient traffic discharge and reduced congestion. The optimized signal cycle was 80 seconds, with the main street (east–west approaches) operating on green, red, and amber times of 40, 35, and 5 seconds, respectively, while the minor street (north approach) operated on 30, 45, and 5 seconds, respectively. The findings indicated that reducing unnecessary waiting times significantly lowers fuel consumption, emissions, and economic costs. Moreover, cost analysis revealed that the ITCS can be implemented with a low budget, making it scalable for other intersections and adaptable to developing countries. By combining affordability, adaptability, and environmentally friendly operation, the proposed ITCS offers a practical and innovative solution for improving urban traffic management.